DESKRIPSI KESALAHAN PENGGUNAAN TANDA BACA DAN EJAAN PADA KARANGAN SISWA KELAS V SEKOLAH DASAR NEGERI 08 PONTIANAK UTARA - Suhardi, Suhardi; Salimi, Asmayani; Suparjan, Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The purpose of this study is to describe: (1) errors in the use of punctuation in the form of (periods, commas and hyphens); (2) spelling errors in the use of capital letters in the essays of grade V Elementary School 08 Pontianak Utara. This research is a qualitative research using descriptive research methods with data sources of the work of class V-A students of SD Negeri 08 Pontianak Utara, totaling 24 people. The instrument in the research is a human instrument, namely the researcher acts as an instrument. Data collection techniques using documentation studies, reading and note- taking techniques. The data analysis technique used is the Tarigan language error analysis technique. The results of this study were 374 errors including errors in the use of capital letters at the beginning of sentences, errors in writing periods at the end of sentences, writing commas in transitive sentences, errors in writing capital letters that do not match Enhanced Indonesian Spelling (EYD), errors in writing periods. which do not comply with the EYD, comma errors that do not comply with the EYD, and incorrect use of hyphens.